2019
DOI: 10.7717/peerj.7316
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic nomogram for neuroblastoma in children

Abstract: Introduction Neuroblastoma is one of the most common extracranial solid tumors in children, which accounts for about 7–10% in children’s tumors. The prognosis group of patients with neuroblastoma could not only improve the efficacy of high-risk patients, but also reduce the effects of drug complications for surviving patients. Material and Methods Patients diagnosed with neuroblastoma between 1986 and 2012 were selected form the TARGET database. The nomogram was built with potential risk factors based on COX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Finally, research comparing the survival rates by race among children with common extracranial solid tumors between 1985 and 2005 reported that black children had a 31% higher risk of death compared with white children [10]. Studies that used other databases than SEER reported inconsistent results with regard to an association between race and survival in children with neuroblastoma [8,[12][13][14]. In the early 1970s, DiNicola et al compared the survival rates of 30 white and 15 black children with neuroblastoma treated at the Children's Hospital National Medical Center in Washington DC [14].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, research comparing the survival rates by race among children with common extracranial solid tumors between 1985 and 2005 reported that black children had a 31% higher risk of death compared with white children [10]. Studies that used other databases than SEER reported inconsistent results with regard to an association between race and survival in children with neuroblastoma [8,[12][13][14]. In the early 1970s, DiNicola et al compared the survival rates of 30 white and 15 black children with neuroblastoma treated at the Children's Hospital National Medical Center in Washington DC [14].…”
Section: Discussionmentioning
confidence: 99%
“…The final adjusted model included age, gender, ethnicity, stage, site, and year of diagnosis. These covariates were identified as being clinically relevant and were sued in previous studies as well [8][9][10][11][12][13][14]. In addition, they were unequally distributed according to the race (Table 1) and the survival.…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 3 more Smart Citations